2013
DOI: 10.1212/wnl.0b013e3182872867
|View full text |Cite
|
Sign up to set email alerts
|

Multiple molecular mechanisms for a single GABA A mutation in epilepsy

Abstract: Objective: To understand the molecular basis and differential penetrance of febrile seizures and absence seizures in patients with the g2(R43Q) GABA A receptor mutation.Methods: Spike-and-wave discharges and thermal seizure susceptibility were measured in heterozygous GABA A g2 knock-out and GABA A g2(R43Q) knock-in mice models crossed to different mouse strains.Results: By comparing the GABA A g2 knock-out with the GABA A g2(R43Q) knock-in mouse model we show that haploinsufficiency underlies the genesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 25 publications
2
74
0
1
Order By: Relevance
“…A single nucleotide substitution caused a highly conserved arginine residue located within a loop between the α-helix and the β1-sheet (the α-β1 loop) in the extracellular N terminus to be replaced by a glutamine (Figure 1A), resulting in impaired surface expression of γ2 subunits and decreased GABA A receptor currents (Bianchi et al, 2002; Kang and Macdonald, 2004; Sancar and Czajkowski, 2004; Hales et al, 2005; Eugene et al, 2007; Frugier et al, 2007). Heterozygous knock-in mice carrying this mutation displayed spontaneous spike-wave discharges and thermal-induced seizures (Tan et al, 2007; Reid et al, 2013), consistent with R82Q being an epilepsy-causing mutation. However, whether this mutation has dominant negative effects on other GABA A receptor subunits and how it affects subunit-subunit interactions is still controversial (Hales et al, 2005; Frugier et al, 2007).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…A single nucleotide substitution caused a highly conserved arginine residue located within a loop between the α-helix and the β1-sheet (the α-β1 loop) in the extracellular N terminus to be replaced by a glutamine (Figure 1A), resulting in impaired surface expression of γ2 subunits and decreased GABA A receptor currents (Bianchi et al, 2002; Kang and Macdonald, 2004; Sancar and Czajkowski, 2004; Hales et al, 2005; Eugene et al, 2007; Frugier et al, 2007). Heterozygous knock-in mice carrying this mutation displayed spontaneous spike-wave discharges and thermal-induced seizures (Tan et al, 2007; Reid et al, 2013), consistent with R82Q being an epilepsy-causing mutation. However, whether this mutation has dominant negative effects on other GABA A receptor subunits and how it affects subunit-subunit interactions is still controversial (Hales et al, 2005; Frugier et al, 2007).…”
Section: Introductionmentioning
confidence: 67%
“…Compared to a hypomorphic allele, the R82Q mutation increased seizure susceptibility indicating that it had effects in addition to haploinsufficiency (Chiu et al, 2008). A recent study also suggested that γ2 subunits haploinsufficiency could account for genesis of absence seizures in γ2 R82Q/+ knock-in mice but not the increased thermal seizure susceptibility, while the R82Q mutation increased thermal seizure susceptibility, independent of genetic background (Reid et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primjerice, animalni model Dravet sindroma temeljen na SCN1A i SCN1B mutaciji pokazuje povećanu osjetljivost na konvulzije 45 . Nadalje, GEFK+ modeli temeljeni na SCN1B i GA-BRG2 mutacijama također pokazuju sklonost konvulzijama prilikom povećanja temperature okoliša 46 . Takva istraživanja su također pokazala o dobi ovisne učinke u pogledu konvulzija induciranim porastom temperature, modelirajući dobno ovisne manifestacije FK-a 47 .…”
Section: Eksperimentalni Modeli Febrilnih Konvulzijaunclassified
“…The fact that GABRB3 truncations have not been reported in the ExAC database argues for the latter hypothesis. It has also been shown that the epileptic phenotype observed in mouse models lacking one allele of a GABA A receptor subunit gene may be milder compared to missense mutation carriers, 38 although this may depend on the functional interactions of the truncated protein and the remaining WT subunits. 39 Lastly, we cannot completely exclude that the parents carry these mutations in a mosaic state, as seen in the mother of patient 9, even though this is not obvious from the blood DNA analysis.…”
mentioning
confidence: 99%